HOLDER DESIGN EVALUATION OF GAMMA AREA MONITOR IN SOLID RADIOACTIVE WASTE INTERM STORAGE ROOM OF RADIOMETALURGY INSTALLATION - Waringin Margi Yusmaman, S.ST, M. Si; Mohamad Sukron Fajrin Husein; Denia Karlina Utami Putri; Kesi Indriana (Reaktor : Buletin Pengelolaan Reaktor Nuklir, 2020)
HOLDER DESIGN EVALUATION OF GAMMA AREA MONITOR IN SOLID RADIOACTIVE WASTE INTERM STORAGE ROOM OF RADIOMETALURGY INSTALLATION. Radiometalurgy Installation (RMI) is one of Non-Reactor Nuclear Installation where post-irradiation examination (PIE) take place, which give gamma radiation ranged from one µSv/h to the order of mSv/h. The PIE activity produce high-activity radioactive waste as a by-product that stored temporarily in RMI Building. The temporary solid radioactive waste storage room is equipped with in situ gamma area monitor (GAM) as a mean of external radiation protection for radioactive waste operator. This research is conducted to understand the characteristic of GAM Detector and evaluate the positioning of detector, the design of detector holder, and the threshold setting of radiation detection alarm in The temporary solid radioactive waste storage room. The research is conducted by measuring a standard radiation source Cs-137 with the activity of 1 µCi using GAM Detector with variation of position in 4 point, which are in the middle-front of detector, the front-side of the detector vessel, the middle of detector vessel, and back-end of detector vessel, along with variation of source to detector distance, which are 0 cm, 10 cm, 20 cm, 30 cm, 40 cm, and 50 cm. The measurement done in the middle-front of the detector give the highest dose of gamma radiation measured which are 5.63, 4.20, 0.58, 0.28 μSv/h. The result of gamma radiation dose measurement by the detector shows that the closer the source to middle-front part of the detector the higher the radiation measured. The holder design of the gamma radiation detector used in the current GAM device provides information on the gamma radiation dose rate of 74.26% of the actual dose rate. The detector holder currently positioned the middle-front side of the detector upwards therefore the design of detector holder needs to be modified in order for the detector to measure the dose more effectively and give the true number of dose measured